King Vajiravudh’s views towards German Influence in Turkey from the Late 19th Century to World War I - Thumruksa, Wasapol (Journal of Humanities and Social Sciences Uttaradit Rajabhat University, 2024)
The objective of this academic article were to examine King Vajiravudh’s views towards the expansion of German influence in Turkey or the Ottoman Empire during the period from the late 19th century to World War I and the impact of such views on German propaganda operations in Siam during World War I. This would help expand the knowledge about King Vajiravudh’s views towards Germany, which past academic works focused only on his views towards the expansion of German influence in Siam. It would also help expand the knowledge about Siam’s role in World War I. The results of this study indicated that King Vajiravudh had negative views towards the expansion of German influence in Turkey. He also viewed the Young Turks, who seized power in Turkey from Sultan Abdul Hamid II, as merely a German puppet. King Vajiravudh believed Turkey did not gain any benefits from its participation in World War I on the German side unlike Germany. Additionally, these views affected German propaganda operation in Siam during World War I because it caused King Vajiravudh to distrust Siamese military officers who graduated from Germany. King Vajiravudh also viewed the dissemination of German propaganda in Siam as an attempt to make Siam become like Turkey.